Modern Applications of Electrostatics and Dielectrics - Xiao, Dengming; Sankaran, Krishnaswamy (IntechOpen, 2020)
Electrostatics and dielectric materials have important applications in modern society. As such, they require improved characteristics. More and more equipment needs to operate at high frequency, high voltage, high temperature, and other harsh conditions. This book presents an overview of modern applications of electrostatics and dielectrics as well as research progress in the field.